Direct NI-CO alloy plating of titanium alloy surfaces by high speed electrodeposition - Hussain, M. S. (2012)
An innovative process for electrodepositing Ni-Co alloy coatings directly on Ti surfaces without the need to carry out the traditional pretreatment of the substrates and pre-plating with an intermediate metallic layer is discussed. Currently in the electroplating industry the naturally occurring oxide layers present on Ti surfaces are first removed by acid etching and the surface plated with a displacement reaction. In this work, by using a turbulent electrolyte flow and by varying the applied current densities, Ni-Co alloy has been electrodeposited directly on Ti surfaces at a plating rate exceeding 700 μm per hour. FESEM and XRD techniques have been used to characterise these coatings. Results confirm that these coatings are homogeneous, nanocrystalline in nature and appear to be well bonded to the substrate without any distortion or cracks at the interface. Currently this method of turbulent solution flow of electrolyte is the only means of obtaining fast rate of electrodeposition directly on titanium surfaces without usual pre-treatment.